EVALUATION OF THYROID PROFILE AND ITS PROGNOSTIC VALUE IN PATIENTS OF ACUTE CORONARY SYNDROME - Thacker, Bhavik; Shrimali, Lalit; Padhiar, Abhishek (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to study the association of thyroid dysfunction with acute coronary syndrome (ACS), its complications and duration of hospital stay. Methods: This prospective comparative study was done on 100 patients divided equally into ACS patients with control (normal thyroid function) and ACS patients with thyroid dysfunction admitted in a tertiary care center, Udaipur, Rajasthan with ACS during the period of February 2021–July 2022. We studied the prevalence, prognostic factor of thyroid hormone in these patients. Results: The mean ejection fraction of the control group was 51.16±11.72%, of hypothyroid group was 49.00±13.55% and of hyperthyroid group was 51.12±13.78%. 29 cases of cardiac failures, 38 cases of arrhythmias, and 32 cases of major adverse cardiac events were observed. 56% of patients required thrombolysis, out of which 67.86% were from the subclinical hypothyroid group. The mean hospital stay in control group was 4.53±1.55, in hypothyroid group was 5.27±1.84 and in hyperthyroid group was 7.00±1.92.18% mortality. Conclusion: Patients with acute myocardial infarction, initially develop alteration in thyroid hormone levels, which is possibly a compensatory mechanism to reduce the metabolic demand of the heart, by reducing myocardium contraction and cardiac output but may cause cardiac failure and higher rates of cardiovascular complications like arrhythmias and death in some of the patients. Thyroid dysfunctions in patients with ACS may also need a longer duration of intensive care and close monitoring during follow-up.